2021
DOI: 10.1155/2021/4434504
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Therapeutic Effects of Chinese Herbal Decoction Combined with Glucocorticoid in Treating Primary Nephrotic Syndrome in Children

Abstract: Background. To investigate the clinical effects of Chinese medicine decoction combined with glucocorticoid in treating children with primary nephrotic syndrome. Methods. A total of 70 children with pediatric nephritis nephrotic syndrome treated at Weifang People’s Hospital from January 2019 to December 2019 were randomly allocated to the therapy group and the control group, each with 35 cases. The control group was treated with conventional Western medicine, and the therapy group received Western medicine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…According to the TCM theory, Liuwei Dihuang pills have the functions of nourishing yin and tonifying the kidneys. In modern research, Liuwei Dihuang pills boost the immune system, improve renal function, and promote metabolism ( Liu et al, 2020 ; Qiu et al, 2020 ; Hou et al, 2021 ). Relevant clinical studies have shown that Liuwei Dihuang pills in combination with hormone therapy in the treatment of LN reduce receptor expression, consequently reducing the advanced glycation end-product levels to avoid further exacerbation of tissue immune responses.…”
Section: Traditional Chinese Medicine Preparations In Lupus Nephritismentioning
confidence: 99%
“…According to the TCM theory, Liuwei Dihuang pills have the functions of nourishing yin and tonifying the kidneys. In modern research, Liuwei Dihuang pills boost the immune system, improve renal function, and promote metabolism ( Liu et al, 2020 ; Qiu et al, 2020 ; Hou et al, 2021 ). Relevant clinical studies have shown that Liuwei Dihuang pills in combination with hormone therapy in the treatment of LN reduce receptor expression, consequently reducing the advanced glycation end-product levels to avoid further exacerbation of tissue immune responses.…”
Section: Traditional Chinese Medicine Preparations In Lupus Nephritismentioning
confidence: 99%
“…The total effective rates of the TCM group and the control group were 93.9 and 75.0%, respectively ( p < 0.05). The recurrence rate in the control group was significantly higher than that in the control group (53.1 vs. 21.1%, p < 0.05) ( Hou et al, 2021 ). Zhang et al conducted a meta-analysis on the treatment of FSGS with the method of supplementing Qi and activating blood circulation.…”
Section: Clinical Studies On Treating Podocytopathies With Tcmmentioning
confidence: 99%
“…Besides, Liuwei Dihuang pill can also be used to treat a variety of other diseases, including type 2 diabetes, [10] postmenopausal osteoporosis, [11] triple negative breast cancer , [12] and Primary nephrotic syndrome. [13] Modern scientific research had confirmed the function of Liuwei Dihuang pill manifested in anti-inflammation, [14] Inhibition of apoptosis, [15] and so on. Numerous papers have shown that Liuwei Dihuang pill has a good clinical effect on tinnitus.…”
Section: Introductionmentioning
confidence: 99%